Insight into Intermolecular Hydrogen Bonding Interaction in the Formation of Paracetamol-caffeine (PCM-CF) Cocrystal - Paneru, Tirth Raj; Bhandari, Basanti; Joshi, Bhawani Datt (Far Western Review, 2024)
In this study, the theoretical screening of cocrystals of paracetamol and caffeine was performed via electrostatic potential (ESP) surface, quantum theory of atoms in molecules (QTAIM), and natural bond orbital (NBO) analysis. This work aims to find the strongest intermolecular hydrogen bonding between paracetamol and caffeine to develop a stable and significant cocrystal for improved performance. ESP analysis showed four possible interactions (O–H…N, N–H…O, O–H…O, and C–H…O) based on H-bond donor (α) and acceptor (β) parameters for caffeine and paracetamol. The screening of these four interactions between paracetamol and caffeine shows that, the PCM-CF cocrystal formed with intermolecular hydrogen bonding interactions O–H…N and O–H…O found to be significant. The intermolecular interaction O–H…O between caffeine and paracetamol has higher interaction energy, as revealed from the ESP, QTAIM, and NBO analysis, showing that this is more beneficial for the formation of PCM-CF cocrystal. The most stable PCM-CF cocrystal was formed by the interaction of the OH group of paracetamol as the H-bond donor group with the H-bond acceptor carbonyl group (C10=O2) of the benzyl ring of caffeine. The energy gap between HOMO and LUMO for the PCM-CF cocrystal generated by O–H…O interaction was found to be 3.82 eV, which is less than that of caffeine and paracetamol. These findings indicate that the reactivity of the PCM-CF cocrystal has increased.